Advancement of Pt and Pd-based catalysis for green, sustainable energy and bio-medical applications - Nithyadharseni Palaniyandy; Sekhosana Kutloano; Lakshmi Devaraj; Xolile Fuku; Sathish Sundar Dhilip Kumar (Current Research in Green and Sustainable Chemistry)
Platinum (Pt) and palladium (Pd) -based catalysts have sparked intense research interest for many important reactions in green energy and sustainable technologies such as key industrial petrochemical processes, fine chemical synthesis, environmental protection, renewable energy conversion and microbial, as their specific activity, stability and selectivity are greatly higher. However, the availability of low-cost electrodes/catalysts with high activity and stable electrochemical performance is crucial for the development of long-term and cost-effective green energy, environmental and sustainable technologies. In response to the growing demand for these products, the development of strategies to produce various materials is being intensified. This review summarizes the recent research efforts to develop advanced noble metal-based electrocatalysts with excellent performance for water splitting catalysis, CO2 reduction, electrochemical sensors and antimicrobial applications. Pt and Pd co-catalysts in photocatalytic water splitting are examined for their contributions to clean hydrogen production, with a focus on bandgap adjustment, reduced recombination time, and enhanced charge carrier separation. The electrochemical reduction of carbon dioxide is also explored, highlighting the selectivity and efficiency of Pt and Pd systems, addressing both carbon capture and the generation of valuable chemicals. Similarly, their role as co-catalysts in photocatalytic carbon dioxide reduction is discussed for improved efficiency and selectivity. The review also addresses Pt- and Pd-based electrochemical sensors, emphasizing their catalytic roles in medical diagnostics and gas sensing. Further, the antimicrobial properties of Pt and Pd nanoparticles are explored, showcasing their potent inhibition of bacterial growth, disruption of biofilm formation, and effectiveness against multidrug-resistant bacteria. Additionally, the unique attributes of metal nanoclusters for biomedical sensing and imaging applications are discussed. Finally, a personal outlook is given to highlight the challenges and opportunities for the development of novel electrocatalysts suitable for a wide range of commercial applications in fostering advancements in sustainable technologies and materials.